The Anxiety as a Trigger of the Repressive Actions in the novel Still Alice - Anik Widya Wati; Rosmiati Rosmiati; Waladdin Panggabean (Prologue: Journal on Language and Literature, 2020)
This research focuses on the anxiety of Alice Howland in the novel Still Alice by Lisa Genova. There are two objectives of this research; 1) to find out the kinds of anxiety on Alice Howland in the novel Still Alice by Lisa Genova and 2) to explain the condition of Anxiety trigger the repressive Actions to Alice Howland in the Novel Still Alice by Lisa Genova. In this research the researcher used the theory is Psychoanalysis by Sigmund Freud that talk about Anxiety and Defend Mechanism; the methodology employed is qualitative and the researcher present the issues descriptively and using the data collected from the novel were taken out as the primary data. The result the research was found the kinds of anxiety that occurred in Alice Howland namely hormonal anxiety, social anxiety and attack anxiety which could trigger repressive actions in Alice Howland and the researcher found several repressive actions in Still Alice's novel, namely repetition, moral felling and composing self.